Chinese Language Translation of the Sipanjimas Application Registration Guidebook for the Banyumas Licensing Service Information System (DPMPTS Banyumas) - Monika Herliana; Henggar Prasetyowati; Puspita Reisy Aryovather; Zhuang Haili (Universitas Negeri Surabaya, 2024)
This article, entitled